The quality of college life (QCL) among hotel and catering students in Malaysian polytechnics / Azian Ismail - Ismail, Azian (2013)
A good quality of college life (QCL) is about the overall judgment of students about their satisfaction towards the academic aspects, social as well as facilities and services provided by the institutions. This study aims to examine the relationship between the quality of college life and academic as well as social aspects and also facilities and services provided. It also determines the most contributing variables to the quality of college life. This study involved 380 students from four Malaysian polytechnics who enrolled in Diploma of Hotel and Catering. The systematic sampling was used to select the sample based on the students’ list as the sampling frame. The study utilized questionnaire as the research instrument. A self-administered questionnaire was adapted from Sirgy, Grzeskowiak and Rahtz (2007). There were 76 items developed to measure the relationship between academic aspects and social aspects as well as facilities and services towards the quality of college life. The respondents were required to answer questionnaires using six points Likert Scale with six point scale from “strongly agree 6” to “strongly disagree 1”. In order to examine the relationship between academic aspects, social, facilities and services towards the quality of college life the multiple regressions were performed. Regression models explained that 55.7% of the variance represented by the quality of college life. The other 44.3% represented by other predictor variables. The coefficient results reported that only facilities and services (p= 0.00 < α = 0.05) and social aspects were significant at (p= 0.02 < α = 0.05) level.